Rapid Development of an Effective Newcastle Disease Virus Vaccine Candidate by Attenuation of a Genotype VII Velogenic Isolate Using a Simple Infectious Cloning System - Wang, Nannan; Huang, Mei; Fung, To Sing; Luo, Qiong; Ye, Jun Xian; Du, Qian Ru; Wen, Liang Hai; Liu, Ding Xiang; Chen, Rui Ai (Frontiers in Veterinary Science, 2020)
Newcastle disease virus (NDV) genotypes or variants even in the vaccinated chickens. In this study, we report attenuation and rapid development of a velogenic NDV isolate as an effective vaccine candidate, using a simple and reliable protocol for construction of an infectious cloning platform.Based on DHN3, a genotype VII velogenic NDV isolate, recombinant rDHN3 was rescued by cotransfection of plasmids expressing the genomic RNA, NDV proteins NP, P and L, and the T7 polymerase without using a helper virus. Subsequently, an attenuated strain rDHN3-mF was produced by substitution of residues from amino acids 112 to 117 of DHN3 F protein with the corresponding sequence from LaSota. Both rDHN3 and rDHN3-mF are genetically stable during propagation in cell culture and chicken embryos. Further characterization through determination of EID50, MDT and clinical assessments confirmed that rDHN3 is velogenic and rDHN3-mF lentogenic. Vaccination of one-week-old SPF chicks with inactivated rDHN3-mF produced much higher anti-DHN3 antibody response and better protection against live DHN3 challenge than did the commercial LaSota vaccine, providing 100% protection and much earlier viral clearance. This attenuated NDV isolate would merit further development into a vaccine product.